Adoption of '1 Must Do - 5 Reductions' rice management practices in Vietnam - CGIAR Research Program on Rice (2018)
In Vietnam, 1 Must 5 Reductions (1M5R) is certified by a Presidential decree (532-QD-TT-CLT) as the national policy to promote best management practices in lowland rice cultivation. The use of 1M5R focused on reduction of seed and pesticide inputs. This management reduced the production costs by 23% reducing the production by 203 US$/ha per season, and generating 19% additional income, 175 US$/ha more. The adoption of this technology was 28% more beneficial compared to farmers who did not follow 1M5R.